Genome-wide analysis and expression profile of PIN-formed auxin carrier genes during in vitro IBA-induced adventitious rooting in Olea europaea L. - Velada, Isabel (2020)
Olive (Olea europaea subsp. europaea var. europaea L.) comprises several cultivars with reduced capacity to be propagated due its recalcitrant behaviour upon adventitious rooting (AR) stimulus. This prevents their propagation and consequently their availability in the nurseries. By overcoming the difficult-to-root behaviour it will be possible to increase the number of cultivars available for new orchards and consequently taking profit of it on final products differentiation. There are many protocols used in vegetative propagation to induce AR based on auxins, a group of phytohormones largely known as involved in many processes of plant development, including root initiation and development. However, most of these protocols are still based on “trial/error” approaches, where several variables needs to be tested. This happens because genetic control underlying AR is not completely elucidated. Auxins are mainly synthesized in young leaves and apical meristem of shoots and roots. The major auxin distribution is regulated by transport from cell to cell, known as polar auxin transport (PAT). PAT is mediated by three main classes of membrane auxin transporters, the auxin resistant 1/like aux1 (AUX/LAX), the ATP binding cassette subfamily B (ABCB/MDR/PGP) and the pin-formed (PIN) carriers. The PIN gene family encodes a subgroup of auxin efflux carriers shown to be involved in various developmental processes, including lateral/adventitious root formation, in several plant species. To date, PIN genes have been identified in 31 plant species by genome-wide approaches, however, there is still no information regarding its identification in olive. The recent publication of O. europaea genome allowed us to perform the identification of all members belonging to PIN gene family in this species (OePIN). Our work aims to characterize OePIN family, as well as, to investigate the involvement of its members during AR. The expression profile study of OePIN members during AR in IBA-induced in vitro cultured microshoots of cv. ‘Galega vulgar’, attempting to understand if the hard-rooting behaviour of this cultivar might be related with a disturbance in auxin transport. Additionally, reactive oxygen species (ROS) as key signaling molecules that regulate growth and development and coordinate responses to biotic and abiotic stresses in plants are also being analysed in IBA-treated and non-treated explants. Also, cells from phloem, cortex and sub-epidermis are being isolated and gene expression will be performed on these cells in order to find out which cells are responsible for the formation of adventitious roots.